Synthesis and Pharmacological Activity of Betulin Dinicotinate - Flekhter, O.B.; Larachurina, L.T.; Nigmatullina L.R.; Sapozhnikova, T.A.; Baltina, L.A.; Zarudii, F.S.; Galin, F. Z.; Galin, F. Z.; Tolstikov, G. A.; Plyasunova, O.A.; Pokrovskii, A.G.
The assignment of NMR resonances of lupane triterpenoids was refined by the example of 3 O ,28 O - dinicotinoylbetulin, obtained by acylation of betulin. Hepatoprotective, antiulcer, antiinflammatory, reparative, and anti-HIV activities were found for the compound. In addition, it was demonstrated to have immunomodulatory activity, for the first time detected among lupane triterpenoids.
Keywords: BETULIN DINICOTINATE; HEPATOPROTECTIVE; IMMUNOMODULATORY; ANTIULCER; ANTI-HIV ACTIVITIES; LUPANE TRITERPENOIDS